Report on ‚The Central & Eastern European Forum 2024’ conference - Pesuth, Tamás; Grébel, Szabolcs (Public Finance Quarterly, 2024)
The Central & Eastern European Forum 2024, organised by Euromoney, took place in Viennafrom 16-17 January 2024.In this report, we shed light on the economic trends and challenges in the region, based on the panel discussions at the two-day Euromoney conference. The conference highlighted a number of key issues and featured a number of leading speakers from government and business. The Forum was one of the largest events organised by Euromoney, with more than 1,500 participants, indicating its growing importance in the CEE region.